Mali : Exporting Mangoes to Europe - Morgane, Danielou (World Bank, Washington, DC, 2012)
European consumers were more likely, until recently, to eat Indian, Israeli or Brazilian mangoes rather than Malian ones. However, since 2001, sea-freighted Malian mangoes produced in the south of the country by small-scale farmers have been successfully exported and retailed in Northern Europe. This achievement was quite significant given the prior failure of similar projects and the overall difficulty in finding investors for the export of perishables from landlocked countries with poor transport connections, like Mali. The export of Malian products is controlled by Ivorian exporters with few returns to the producers on the other side of the border. Despite the high quality of its fresh fruit and vegetables, the high cost of airfreight was impeding the expansion of production and export. By establishing a multi-modal shipment system and improving every step of the supply chain, the mango export pilot project proved the feasibility and profitability of such innovation.